Fintech Payment, Literasi Keuangan, dan Pendapatan Orang Tua terhadap Perilaku Pengelolaan Keuangan Pribadi pada Generasi Z di Unjani - Debby Claudyaputri Gunawan; Novi Susyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to investigate the influence of fintech payment, financial literacy, and parental income on financial management behavior among Generation Z students at Jenderal Achmad Yani University (UNJANI). In the era of globalization marked by rapid technological advances, students' financial behavior is becoming increasingly important, especially for the technology-savvy generation. This study identifies the challenges faced by students in managing their finances, such as impulsive spending and lack of financial planning skills, despite support from parents. Quantitative methods were used by collecting data through questionnaires from 100 students. The results of the analysis showed that fintech payment and financial literacy had a significant positive effect on financial management behavior, while parental income did not show a significant effect. The resulting regression model explained 55.4% of the variance in financial management behavior. This study emphasizes the importance of increasing financial literacy and the use of responsible fintech services to improve financial management behavior among students. Keywords: Fintech Payment, Financial Literacy, Parental Income